The effect of high-intensity interval training and moderate-intensity continuous training on aerobic fitness and body composition in males with overweight or obesity: A randomized trial. (March 2020) - Ram, Adrian; Marcos, Lauren; Jones, Matthew D.; Morey, Robert; Hakansson, Stefan; Clark, Tomasin; Ristov, Michael; Franklin, Aysha; McCarthy, Chris; De Carli, Leal; Ward, Rachel; Keech, Andrew
Abstract: The optimal exercise training characteristics for improving body composition in individuals with obesity are not clear. This study assessed the effects of 6-weeks of high-intensity interval training (HIIT) or moderate-intensity continuous training (MICT) on aerobic fitness and body composition in males with overweight or obesity. Twenty-eight participants (18–45 years; BMI: 25–35 kg/m 2 ) performed stationary cycling 3 times per week for 6 weeks. Participants were randomly allocated to work-matched HIIT (N = 16) (10 × 1-min intervals at ~90% peak heart rate) or MICT (N = 12) (30 min at 65–75% peak heart rate). Maximal aerobic capacity (VO2 peak) and body composition were assessed before and after 6-week training. Both HIIT and MICT induced moderate increases in aerobic fitness (Δ% VO2 peak: HIIT 9 ± 8%, ES = 0.42; MICT: 7 ± 13%, ES = 0.32) and work capacity (Δ% peak workload: HIIT 13 ± 10%, ES = 0.69: MICT 17 ± 15%, ES = 0.76), but these changes did not differ significantly between the groups (all p > 0.16). The effects of HIIT or MICT on body composition outcomes were negligible to small across whole-body and all regional-specific sites (all effect sizes ES = −0.19 to 0.38) and did not differ significantly between the groups (all p > 0.21). Short-term (6-weeks) cycling training did not improve body composition in males with overweight or obesity. Improvements in aerobic fitness were comparable between work-matched HIIT and MICT. Highlights: What is already known about this subject? Aerobic exercise training can improve body composition via reduced body fat levels and increased aerobic fitness. What this study adds: Short-term (6 weeks) cycling training was not effective for reducing body fat levels in males with overweight or obesity, irrespective of training intensity. Improvements in aerobic fitness were comparable following work-matched HIIT or MICT. Research or clinical implications: Exercise programming for clients with obesity should not include short-term cycling training for the goal of inducing fat loss but it is suitable if aerobic fitness is the desired training goal.